A etnização em Caxias do Sul : a construção da narrativa da "diversidade" no desfile da Festa Nacional da UVA de 2014 - Branchi, Ana Lia Dal Pont (My University, 2016)
The main objective of the present dissertation is to investigate the meaning of the insertion of the theme of cultural diversity on the Festa da Uva 2014 parade at Caxias do Sul. The parade was chosen as the field of study of the research because it is the moment where mainly the representation of italianity – Italian immigrant as civilizing heroes that built Caxias do Sul through work – and with greater strength, since the parades of the decade of 90, in which the 120 years of Italian immigration was celebrated. Starting from the Festa da Uva of 2006 the process of inclusion of the cultural diversity theme has begun with the insertion of representations related to other social groups that would also have built the city of Caxias do Sul. In order to accomplish the objectives of the research it has necessary to understand the complex concept of identity, through the preparation of a theoretical framework, as well as the development of an overview about the transformations of identity in Caxias do Sul. Said data added to the analysis of the interview with the informants that participated of the Festa da Uva 2014 parade allowed the comprehension of the layers of significates existing in the identity phenomenon on the city and the identification of the meanings present in the diversity.
A presente dissertação tem como objetivo principal a investigação dos significados da inserção do tema da diversidade cultural no desfile da Festa da Uva 2014, em Caxias do Sul. O desfile foi escolhido como campo de estudo para a pesquisa por ser um momento em que se manifestam principalmente as representações da italianidade – imigrantes italianos como heróis civilizadores que construíram Caxias do Sul através do trabalho - e com maior força, desde os desfiles da década de 90, em que se comemoraram os 120 anos de imigração italiana. A partir da Festa da Uva de 2006 iniciou-se um processo de inclusão do tema da diversidade cultural, com a inserção de representações referentes a outros grupos sociais que também teriam construído a cidade de Caxias do Sul. Para atingir os objetivos da pesquisa foi necessária a compreensão do complexo conceito de identidade, através da elaboração de um referencial teórico, bem como o desenvolvimento de um panorama sobre as transformações da identidade em Caxias do Sul. Estes dados somados às análises das entrevistas com informantes participantes do desfile da Festa da Uva 2014 permitiram a compreensão das camadas de significados presentes nos fenômenos identitários na cidade e a identificação dos significados presentes na diversidade.
Keywords: Pluralismo cultural; Etnologia; Festa da uva; Caxias do Sul (RS) - História; Cultural pluralism; Ethnology; Caxias do Sul (Brazil) - History